A prospective cohort study on the association between coffee drinking and risk of non-gallstone-related acute pancreatitis. Issue 10 (18th March 2016) - Oskarsson, Viktor; Sadr-Azodi, Omid; Orsini, Nicola; Wolk, Alicja
Abstract: Only one previous study has examined the association between coffee consumption and risk of acute pancreatitis, and it found a reduced risk for alcohol-related episodes among high consumers of coffee. Therefore, we examined (1) the association between coffee consumption and risk of non-gallstone-related acute pancreatitis and (2) whether this association was modified by alcohol intake. Data were obtained from two prospective cohorts, the Cohort of Swedish Men and the Swedish Mammography Cohort, including 76 731 men and women (born 1914–1952). Coffee consumption was assessed at baseline with a FFQ, and the cohorts were followed up between 1998 and 2012 via linkage to national health registries. Hazard ratios were estimated using Cox models, with adjustment for potential confounding factors. During 1 035 881 person-years of total follow-up, 383 cases (246 in men and 137 in women) of incident non-gallstone-related acute pancreatitis were identified. Overall, and irrespective of whether a categorical or a continuous exposure model was used, we observed no association between coffee consumption and risk of non-gallstone-related acute pancreatitis (e.g. the multivariable-adjusted hazard ratio for each 1 cup/d increase in coffee consumption was 0·97; 95 % CI 0·92, 1·03). There was no evidence of effect modification by alcohol intake ( P interaction =0·77). In conclusion, coffee consumption was not associated with risk of non-gallstone-related acute pancreatitis in this large prospective cohort study. Because of the limited number of epidemiological studies and their conflicting results, further research is needed to elucidate this potential association.